2005
DOI: 10.1152/ajpendo.00505.2004
|View full text |Cite
|
Sign up to set email alerts
|

Early dietary intervention: long-term effects on blood pressure, brain neuropeptide Y, and adiposity markers

Abstract: Early life nutrition impacts on subsequent risk of obesity and hypertension. Several brain chemicals responsible for both feeding and cardiovascular regulation are altered in obesity. We examined effects of early postnatal overnutrition on blood pressure, brain neuropeptide Y (NPY), and adiposity markers. Rat pup litters were adjusted to either 3 or 12 male animals (overnutrition and control, respectively) on day 1 of life. After weaning, rats were given either a palatable high-fat diet or standard chow. Small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
109
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 53 publications
(55 reference statements)
15
109
2
1
Order By: Relevance
“…CD-fed rats had elevated plasma adiponectin at 15 weeks regardless of nutrition in early life. This is in line with previous studies in Sprague-Dawley rats, 51 and mice where circulating adiponectin levels increased following 10 weeks of a high-fat diet (HFD), before decreasing after 18 weeks of HFD consumption. 52 Hence, although plasma levels of adiponectin have been reported to be significantly reduced in rodents and humans with established obesity/ diabetes, 17,20 this may depend on the duration of disease.…”
Section: Discussionsupporting
confidence: 92%
“…CD-fed rats had elevated plasma adiponectin at 15 weeks regardless of nutrition in early life. This is in line with previous studies in Sprague-Dawley rats, 51 and mice where circulating adiponectin levels increased following 10 weeks of a high-fat diet (HFD), before decreasing after 18 weeks of HFD consumption. 52 Hence, although plasma levels of adiponectin have been reported to be significantly reduced in rodents and humans with established obesity/ diabetes, 17,20 this may depend on the duration of disease.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study therefore suggest that, at least in male offspring, the programming effects of maternal palatable diets on subsequent food preferences can potentially be ameliorated by eliminating the junk food stimulus from weaning to adulthood (39). The importance of prolonged chow intake postweaning has also been demonstrated in a study by Velkoska et al (60), which focused on offspring reared in small litters to induce early postnatal overnutrition, rather than exposure to a high-fat or cafeteria diet. This study demonstrated that when the offspring from small litters were weaned onto a standard diet until adolescence, they remained fatter and had higher plasma leptin concentrations than those from normal-sized litters.…”
Section: Potential Reversibility Of Programmed Effectssupporting
confidence: 52%
“…This study demonstrated that when the offspring from small litters were weaned onto a standard diet until adolescence, they remained fatter and had higher plasma leptin concentrations than those from normal-sized litters. However, when both groups were provided with standard diet until adulthood, there were no longer any differences in body weight, body composition, or plasma leptin concentrations between the groups (60).…”
Section: Potential Reversibility Of Programmed Effectsmentioning
confidence: 94%
“…Of interest, in contrast to several vascular disease states (Luff et al, 2005), sympathetic innervation density is unchanged in obese rat saphenous artery (Supplemental Table S1), suggesting that sympathetic plexus density does not contribute to the mild hypertension in the diet-induced rodent model (Velkoska et al, 2005) examined in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…Using a well characterized rodent model of diet-induced obesity associated with elevated blood pressure, insulin, and leptin that directly reflects the etiology human dietary obesity (Velkoska et al, 2005;Chen et al, 2009), the effect of chronic obesity on endothelium-dependent vasodilation in the small saphenous artery was examined. The hypothesis tested was that the mechanism of endothelium-dependent vasodilation would be altered in obesity-induced vascular disease, with K Ca and MEGJ components being upregulated.…”
Section: Introductionmentioning
confidence: 99%